2020
DOI: 10.21203/rs.3.rs-45450/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Nurses Towards the Prevention and Control of COVID-19

Abstract: Background: Coronavirus disease 2019(COVID-19) has been spreading globally, with severe impacts on health and economies. Nursing is an essential component of medical care, and nurses’ knowledge, attitude, and practice (KAP) about the prevention and control of the disease directly affects patient’s outcomes ,but there is little know about the nurses’ KAP during the COVID-19 epidemic.Methods: An anonymous survey was conducted using customized questionnaires designed by Sojump platform. 1323 nurses in Wuhan were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…This finding is inconsistent with the previous study of ZhengjiangJin et al in China. 28 In the study of China, nurses had better knowledge on COVID-19 in comparison to current study. The difference might be due to the sources of information about COVID-19 were not available or differences in educational background or different healthcare context.…”
Section: Discussionmentioning
confidence: 50%
“…This finding is inconsistent with the previous study of ZhengjiangJin et al in China. 28 In the study of China, nurses had better knowledge on COVID-19 in comparison to current study. The difference might be due to the sources of information about COVID-19 were not available or differences in educational background or different healthcare context.…”
Section: Discussionmentioning
confidence: 50%
“…Based on the results of the literature search found 21 articles (Table 1) generally assessed the knowledge, attitudes, practices, perceptions, anxiety, and psychological responses of nurses related to COVID-19. Four articles were found in China (Chen et al, 2020;Huang et al, 2020;Jin & Yi, 2020;Li et al, 2020), two in Arabian (Al-Dossary et al, 2020;Alreshidi, 2020), two in India (Adhikari et al, 2020;Patidar et al, 2020), one in Nepal (Kafle et al, 2020), three in Turkey (Aydin & Balci, 2020;Gumus & Basgun, 2020;Semerci et al,2020), one in Northern Ethiopia (Tadesse et al, 2020), two in Pakistan (Alwani et al, 2020;Zafar et al, 2020), one in Iran (Nemati et al, 2020), one in Lebanon (Saadeh et al,2020), one in Ghana (Buertey et al, 2020), one in Indonesia (Sahar et al, 2020), one in Bangladesh (Saha, et al, 2020), and one in Egypt (Goda Elbqry, 2020). The number of samples between 85-1.323 nurses, using a questionnaire as an instrument, the study used a cross-sectional study.…”
Section: Resultsmentioning
confidence: 99%
“…There are nine studies on nursing practice related to COVID-19, including; research in Wuhan China, the study results show nurses have good practices in personal protection, hand hygiene, pre-diagnosis and triage, patient management, and training on infection in hospitals, implementing practical precautions such as proper use of PPE, strict hand hygiene measures, established fever clinics, isolation wards, and designated hospitals. However, this research shows a mismatch between attitudes and practices in standard precautionary measures, proper ward division, strict environmental disinfection, proper disposal of medical waste, and occupational exposure emergency response (Jin & Yi, 2020). Research in Turkey showed as many as 278 (67%) nurses have good infection prevention practices (Tadesse et al, 2020).…”
Section: Practice Related To Covid-19mentioning
confidence: 90%
See 2 more Smart Citations